Shark scales (Pisces: Chondrichthyes) of Pirabas Formation (Eomiocen), Pará, Brazil - de Oliveira, Samantha Florinda Cecim Carvalho; Toledo, Peter Mann de; Costa, Sue Anne Regina Ferreira da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
The lack of stratigraphic localization of shark fossils collected in the Pirabas Formation has made it difficult to use them in paleoecological interpretation and distribution in time. As a way to fill this gap in our knowledge, the screenwashing technique was used in 14 samples, stratigraphically controlled and hailing from the B17 mine (CIBRASA S/A), in Capanema. This provided the first collection and description of shark scales. There are 400 specimens, which can be divided into seven morphotypes according to the format and topography found on the dental crown. These morphotypes were found in all levels and they belong to the orders Orectolobiformes, Carcarhiniformes and Lamniformes, that were already described from the Pirabas Formation and confirm the shallow, marine and tropical environment.
Keywords: Pirabas Formation; Scales; Sharks